Atmospheric variability of methane over Pakistan, Afghanistan and adjoining areas using retrievals from SCIAMACHY/ENVISAT. (December 2015) - ul-Haq, Zia; Tariq, Salman; Ali, Muhammad
Abstract: In the present work we have studied spatial and temporal variability of methane total column (MTC) over Pakistan and neighboring regions of Afghanistan, India and Iran by using observations of SCanning Imaging Absorption SpectroMeter for Atmospheric CHartographY (SCIAMACHY) aboard EOS ENVISAT. Satellite measurements show large spatio-temporal variations in MTC over the study domain at different time scales. We find an average MTC of 1787±22 ppb (annual average±standard deviation) with 3.7% ( slope 7.14±1.28, y-intercept 1751±7.19, r =0.91) increase during the period of January 2003 to April 2012. An enhanced MTC is observed mostly over the Indo-Gangetic Plain and areas with high anthropogenic activities. MTC exhibits a seasonal peak of 1804±28 ppb in summer followed by autumn (1800±25 ppb) and winter (1777±24 ppb). We have also discussed anthropogenic emission estimates in the study area obtained from EDGAR database. Substantial increments of 77% and 61% are observed in anthropogenic CH4 emissions for Pakistan and Afghanistan, respectively, during 1990–2008. Anthropogenic CH4 emissions from enteric fermentation and livestock sectors are found to be the highest. EDGAR data have also identified megacity Lahore, Sukkur, megacity Karachi, Dera Ghazi Khan, megacity Delhi and Ahmedabad as large point sources of CH4 emissions in the region. The emissions from Karachi show the highest increase of 107%, while Lahore is found with the highest annual average emissions of 8.8×10 −10  kg m −2  s −1 . Highlights: This paper analyzes spatio-temporal variations of CH4 over Pakistan and Afghanistan. CH4 variability is discussed for its linkage with meteorology and transportation. Large point sources of CH4 emissions in the study region have been discussed.